1984
DOI: 10.1111/j.1475-6803.1984.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationarity of Beta and Tests of Market Efficiency

Abstract: Conclusions from event type studies are usually supported by data generated from some form of the market model. This study examines the robustness of these conclusions to different static and dynamic estimates of beta when the event under investigation occurs during a period of changing systematic risk. The results indicate that when beta is nonstationary, the findings of market inefficiency (or efficiency) in previous studies may be an artifact of the static beta estimation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The greater the amount and significance of instability, the more doubt is cast on early studies that have (often implicitly) relied on parameter stability. Examples are studies of market efficiency [29] or those using the cumulative residuals technique [25]. To the extent that the techniques used here are capable of identifying shift points and stable regimes, the problem of nonstationarity can be reduced by using timedependent parameters, and more accurate studies are possible.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the amount and significance of instability, the more doubt is cast on early studies that have (often implicitly) relied on parameter stability. Examples are studies of market efficiency [29] or those using the cumulative residuals technique [25]. To the extent that the techniques used here are capable of identifying shift points and stable regimes, the problem of nonstationarity can be reduced by using timedependent parameters, and more accurate studies are possible.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, stock price movements are become more varying and have an effect on the difficulty of predicting the returns of securities because they become unstable all the time [11]. The consequences of the difficult conditions of predicting returns are that the distribution of historical data in the stock market tends to be non-normal [19]), clustered volatility [7]), heteroskedastic [15], and nonstationary [13], [14).…”
Section: Rit -Rft = αI + Bi(rmt -Rft) + Sismbt + Hihmlt + Mimomt + εImentioning
confidence: 99%
“…Eighteen months of post-announcement data were needed to calculate the t + 1 through t + 18 residual returns. Therefore, the sample included no stock announcement dates that occurred after June 1975 ( - 18). The maximum number of monthly portfolios that could have been formed was 175 'Since the Nichols and Brown [ZO] study reported market inefficiencies in the 1968 to 1975 period (the late period), the Group I securities were further split into early and late periods.…”
Section: Endnotesmentioning
confidence: 99%